Moving object detection in noisy video sequences using deep convolutional disentangled representations. - García-González, Jorge; Luque-Baena, Rafael Marcos; Ortiz-de-Lazcano-Lobato, Juan Miguel; López-Rubio, Ezequiel (My University, 2022)
Noise robustness is crucial when approaching a moving de- tection problem since image noise is easily mistaken for movement. In order to deal with the noise, deep denoising autoencoders are commonly proposed to be applied on image patches with an inherent disadvantage with respect to the segmentation resolution. In this work, a fully convolutional autoencoder-based moving detection model is proposed in order to deal with noise with no patch extraction required. Different autoencoder structures and training strategies are also tested to get insights into the best network design ap- proach.
Universidad de Málaga. Campus de Excelencia Internacional Andalucía Tech.
Keywords: Procesado de imágenes; Moving Object Detection; Foreground Segmentation; Autoencoders